A Comparative Study of Higher Degree Students’ Financial Literacy Critical Factors of by Using Analytic Hierarchy Process - Khresna Bayu Sangka; Renata Zoraifi; Nurhasan Hamidi; Sigit Santosa (Politeknik Negeri Batam, 2020)
2018 Global Competitiveness Index 4.0 ranking - a comprehensive report released by the World Economic Forum (WEF) shown that Indonesia's competitiveness ranking was increase from 47 to 45 from the other 140 countries. This condition explained that Indonesian economy was getting better, but it was not enough to compete against other countries, as Indonesian economy was relatively far below the trend line. Furthermore, Indonesian should be more selective in choosing offered products or services especially on banking and finance related sector in which becoming vigilant in investing. One of the intelligence that must be possessed by every individual was financial intelligence in which should be needed by their personal financial assets. This study aimed to explore the determinants of financial literacy in higher degree students by using Analytic Hierarchy Process as an analytical tool. As individual finance’s approved by knowledge, decisions and implementation in making decisions in personal financial assets are called financial literacy. Financial literacy has grown rapidly over the past few years. There are five domains of financial literacy, namely (1) knowledge of financial concepts; (2) communication ability on financial sector; (3) the personal ability to financial management; (4) ability to make financial decisions; and (5) commitment to make future financial planning. Taking Accounting Education Department student as focus of study, the comparison of assessment from identified factors in different classes could be used as a basis for improving the learning process through the development of higher education’s curriculum policies. Result of this study shown that there were insignificant differences between classes. While personal ability to financial management factor considers as the most important factor, followed by the knowledge of financial concept. Both factors are compulsory to be taken as part of financial majors in the department